Regolazione dell'orologio circadiano nei mammiferi mediante SUMOylazione dell'attivatore trascrizionale BMAL1 - Giordano, Francesca; Tota, Bruno (My University, 2006)
4 Abstract The molecular machinery that governs circadian rhythmicity is based on clock proteins organized in regulatory feedback loops. Although posttranslational modification of clock proteins is likely to finely control their circadian functions, only limited information is available to date. Here, we show that BMAL1, an essential transcription factor component of the clock mechanism, is SUMOylated on a highly conserved lysine residue (Lys259) in vivo. BMAL1 shows a circadian pattern of SUMOylation that parallels its activation in the mouse liver. SUMOylation of BMAL1 requires and is induced by CLOCK, the heterodimerization partner of BMAL1. Ectopic expression of a SUMOdeficient BMAL1 demonstrates that SUMOylation plays an important role in BMAL1 circadian expression and clock rhythmicity. This reveals an additional level of regulation within the core mechanism of the circadian clock.
Keywords: Fisiologia animale; Mammiferi